Local Governments Accountability: A Content Analysis of the Financial Audit Reports - Salle, Agustinus (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research examines the financial accountability of local governments, based on the audited Regional Government Financial Statements. Data collected from the financial statements focussed on the village funds transferred from the Central Government to local governments in Papua Province, Indonesia. The regional authorities function as intermediaries to transfer the funds to villages. For analysis, the research applies a qualitative content analysis, using criteria from the Government Financial Accounting Standards (GFAS). The analysis reveals that financial reports still have many deficiencies; almost all reports do not utilise the GFAS. The study resolves that insufficiencies of reporting indicate the shortfall of financial accountability.